Prediction and experimental validation of electrical percolation by applying a modified micromechanics model considering multiple heterogeneous inclusions - Kim, Seong Yun; Noh, Ye Ji; Yu, Jaesang (ELSEVIER SCI LTD, 2015)
Classical micromechanics modeling cannot capture the effect of percolation threshold at a low volume fraction of conductive fillers, even though multiple heterogeneities are considered in the modeling to investigate the effect of reinforcement dispersion, electrical tunneling behavior, and conductive networks. In this study, an analytical homogenization approach for composites containing multiple heterogeneities with conductive coated layers was developed in order to predict the percolation threshold effect, the tunneling effect using hard/soft core concept, and the effective electrical conductivity of polymer matrix composites (PMCs) containing randomly oriented ellipsoidal inclusions coated by conductive layers. The electrical conductivities of polymerized cyclic butylene terephthalate (pCBT)-based composites containing nanofillers such as carbon blacks (CBs), graphene nanoplatelets (GNPs), and carbon nanotubes (CNTs) were prepared by the recently developed composite manufacturing processing using solvent-free powder mixing and in-situ polymerization for inducing uniform dispersion of nanofillers of various shapes and dimensions within a polymer matrix. When comparing the experimentally measured electrical conductivities of those composites with the predicted values obtained from the developed micromechanics models, it is confirmed that the developed approach successfully captures the percolation threshold and the tunneling effect of reinforcements on the effective electrical conductivities of composites containing various shapes of reinforcements. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: THERMAL-CONDUCTIVITY; ENHANCED DISPERSION; COMPOSITES; BEHAVIOR; NANOCOMPOSITES